Çatılı kranların mexanizmlərinin layihələndirmə üsullarının tədqiqi (çatılı kranların təhlükəsiz istismarının ümumi prinsiplərinin analizi, çatılı kranların yükqaldırma mexanizmlərinin konstruksiya olunması variantlarının müqayisəli analizi, çatılı kranların hərəkət mexanizmlərinin və onların arabacıqlarının konstruksiya olunması variantlarının müqayisəli analizi) - Hüseynov, Pərviz; Lətifli, Elvin; Həsənov, Cəmaləddin (My University, 2024)
In the dissertation, expressions are provided for determining safety factors for the strength of individual elements of overhead cranes, based on quantitative analysis of the effect of failure risk on load-carrying capacity using the "load-strength" model. The analysis method for failure risk assumes that load-carrying capacity and resistance follow a normal distribution. Potential damage from hazardous events is considered to estimate safety margins.
Research on Design Methods for Overhead Crane Mechanisms (Analysis of the general principles of safe operation of overhead cranes, Comparative analysis of design options for overhead crane lifting mechanisms, Comparative analysis of design options for overhead crane movement mechanisms and their trolleys)
Keywords: Heavy lifting machinery; Overhead crane